THE ANALYSIS OF FACTORS THAT INFLUENCE ECONOMIC GROWTH IN OKI - Wheni Yeisa; Lina Nugraha Rani (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Economic growth is an indicator that plays an important role in determining the prosperity of a country. This study aims to analyze the effect of labour force, international trade, and inflation towards economic growth in OIC countries over the period 2007 to 2018. Panel data regression analysis approach was adopted to analyze the effect of independent variables on the dependent variable. The results of the fixed effect estimation model found that all variables simultaneously had a significant effect on economic growth. Partially, labour force and internasional trade have a significant effect, while inflation has no significant effect on economic growth. The results of this study can be used as a reference and evaluation materials for policy makers.Keywords: Labour Force, International Trade, Inflation, Economic Growth, Organizations of Islamic CooperationREFFERENCE Ahmad Bhat, Shariq dan Mahboob R.L. (2017). Interest rate, inflation rate, and gross domestic product of India. International Journal of Technical Research & Science, 1(9), 284-288. Al-Faizin, Abdul Wahid, dan Nashr Akbar. (2018). Tafsir ekonomi kontemporer: Menggali teori ekonomi dari ayat-ayat al-qur’an. Jakarta: Gema Insani.Amir, H., Khan, M., & Bilal, K. (2015). Impact of educated labor force on Economic growth of Pakistan: A human capital perspective. European Online Journal of Natural and Social Sciences, 4(4), 814–831.Atoyebi et al. (2012). Foreign trade and economic growth in Nigeria: An empirical analysis. American Academic and Scholarly Research Journal, 4(5), 1-12. Cahyadin, Malik dan Sarmidi, Tamat. (2019). The Impact of foreign direct investment, labour force, and external debt on economic growth in Indonesia and Malaysia. Jurnal Ekonomi Malaysia, 53(1), 171-185.Halim, Abdul M. (2018). Teori ekonomi makro, edisi ketiga. Bogor: Mitra Wacana Media.Iqbal, Nasir and Saima, Nawaz. (2010). Investment, inflation and economic growth nexus. Munich Personal RePEc Archive No. 27163, posted 02 Dec 2010.Ibn Khaldun. (2011). Muqadimmah: terj. Masturi Irham, dkk. Jakarta: Pustaka Al-Kautsar.International Labour Organization (https://www.ilo.org/global/topics/forced-labour/) diakses 10 Februari 2020)Iskandar, Putong. (2013). Economics, pengantar mikro dan makro, edisi kelima. Jakarta: Mitra Wacana Media.ILO, OECD & World Bank Group. 2015. The contribution of labour mobility to economic growth. G20 labour and employment ministers’ meeting. Turkey.Kasmir. (2013). Perbankan Syariah. Jakarta: Kencana.Kementerian Agama Republik Indonesia. (2020). Al-Qur’an dan terjemahan (https://quran.kemenag.go.id), (diakses 15 Januari 2020)Kim, D.-H., & Lin, S.-C. (2009). Trade and growth at different stages of economic development. Journal of Development Studies, 45(8), 1211-1224.Kovac, Ivana. (2013). The influence of international trade of goods of the Republic of Croatia. Journal of Enterprising Communities: People and Places in the Global Economy, 7(1), 60-73. DOI: https://doi.org/10.1108/17506201311315617 Manulang, M. (2013). Manajemen sumber daya manusia. Bandung: Cipta Pustaka Media Perintis.Mohseni, M., & Jouzaryan, F. (2016). Examining the Effects of Inflation and unemployment on economic growth in Iran (1996-2012). Procedia Economics and Finance, 36(16), 381–389.Muhammad, Qazi dan Hye, Adnan. (2012). Exports, imports and economic growth in China: an ARDL analysis. Journal of Chinese Economic and Foreign Trade Studies, 5(1), 42-55.Munir, Qaiser, M. Kasim, & F. Furuoka. (2009). Inflation and economic growth in Malaysia. A threshold regression approach. ASEAN Economic Bulletin, 26(2), 108-93.Murni, Asfia Murni. (2013). Ekonomika makro. Bandung: PT. Refika Aditama. Organization of Islamic Cooperation (online) (https://www.oic-oci.org, diakses 10 Januari 2020)Pujoalwanto, Basuki. (2014). Perekonomian Indonesia: Tinjauan historis, teoritis, dan empiris. Yogyakarta: Graha Ilmu.Raghutla, C., & Chittedi, K. R. (2020). Is there an export- or import-led growth in emerging countries? A case of BRICS countries. Journal of  Public Affairs, 1-12. DOI: https://doi.org/10.1002/pa.2074Rahardjo Adisasmita. (2013). Teori-teori pembangunan ekonomi, pertumbuhan ekonomi dan pertumbuhan wilayah, cetakan pertama. Yogyakarta: Graha Ilmu.Rozalinda. (2014). Ekonomi Islam teori dan aplikasinya pada aktivitas ekonomi. Jakarta: Raja Grafindo Persada.Sidra, Nazir et al. (2017). Threshold modeling for Inflation and GDP Growth. Munich Personal RePEc Archieve.S. H. Manulang. (2010). Pokok-pokok hukum ketenagakerjaan di Indonesia. Jakarta: Rineka Cipta.Shihab, M. Quraish. (2017). Tafsir al-misbah (pesan, kesan, dan keserasian Al-Qur’an), Vol 5 . Jakarta: Pelita Hati.__________________. (2017). Tafsir al-Misbah (Pesan, Kesan, dan Keserasian Al-Qur’an), Vol 6. Jakarta: Pelita Hati.__________________. (2017). Tafsir al-Misbah (Pesan, Kesan, dan Keserasian Al-Qur’an), Vol 10. Jakarta: Pelita Hati.__________________. (2017). Tafsir al-Misbah (Pesan, Kesan, dan Keserasian Al-Qur’an), Vol 14. Jakarta: Pelita Hati.Shochrul R, Ajija, dkk. (2011). Cara cerdas menguasai E-Views. Jakarta: Salemba Empat.Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC). (2019). OIC economic outlook 2019, mobilizing financial resources for development. Publication Department, SESRIC.Sugiyono. (2017). Metode penelitian kuantitatif, kualitatif dan R&D. Bandung: CV Alfabeta.Sukirno, Sadono. (2013). Makro ekonomi: Teori pengantar, edisi ketiga. Jakarta: Penerbit Rajawali Pers.Suparmoko, M dan Sofilda, E. (2017). Pengantar ekonomi makro, edisi 5. Bogor: In Media.Sustainable Development Goals (2017) (https://www.un.org/sustainabledevelopment/ diakses 10 Februari 2020)Syauqi, Irfan. (2016). Ekonomi pembangunan syariah. Jakarta: PT Raja Grafindo Persada.Thanh, S. D. (2015). Threshold effects of inflation on growth in the ASEAN-5 countries: A PSTR approach. Journal of Economics, Finance and Administrative Science, 20(2015), 41–48.United Nations Statistics Division (2017) (https://www.un.stats.org/ diakses 29 Februari 2020).Widarjono. Agus. 2018. Ekonometrika teori dan aplikasi untuk ekonomi dan bisnis. Yogyakarta: Ekonisia.World Bank (https://data.worldbank.org/indicator, diakses 15 Januari 2020)Xiao, J. (2009). The Relationship between inflation and economic growth of China: Empirical study from 1978 to 2007. Lund University School of Economic and Management.Yakubu, M. M., Akanegbu, B. N., & Jelilov, G. (2020). Labour force participation and economic growth in Nigeria. Advances in Management & Applied Economics, 10(1), 1-14.